1997
DOI: 10.1083/jcb.139.5.1219
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Muscle Defects in Mice Lacking Adult Myosin Heavy Chain Genes

Abstract: The three adult fast myosin heavy chains (MyHCs) constitute the vast majority of the myosin in adult skeletal musculature, and are >92% identical. We describe mice carrying null mutations in each of two predominant adult fast MyHC genes, IIb and IId/x. Both null strains exhibit growth and muscle defects, but the defects are different between the two strains and do not correlate with the abundance or distribution of each gene product. For example, despite the fact that MyHC-IIb accounts for >70% of the myosin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 36 publications
6
88
0
Order By: Relevance
“…Since MyHC is a major determinant of the maximum unloaded shortening velocity of skeletal muscle contraction, the type of MyHC comprising a sarcomere is of functional significance (2,3,24,26,29,36). Consistent with the latter concept, a functional analysis of skeletal muscle from either MyHC IIb or MyHC IIx/d null mice revealed altered contractile properties that were unique to each null mutation (1,25).…”
mentioning
confidence: 52%
“…Since MyHC is a major determinant of the maximum unloaded shortening velocity of skeletal muscle contraction, the type of MyHC comprising a sarcomere is of functional significance (2,3,24,26,29,36). Consistent with the latter concept, a functional analysis of skeletal muscle from either MyHC IIb or MyHC IIx/d null mice revealed altered contractile properties that were unique to each null mutation (1,25).…”
mentioning
confidence: 52%
“…18 Inactivation of the genes encoding adult fast skeletal myosin heavy chain IIb and IId/x and creation of MyHC IIx and MyHC IIb null mice have indicated that these genes are required for the normal muscle development and function of adult skeletal muscle in the mouse. [28][29][30][31][32] MyHC IId/x null mutants showed growth inhibition, muscle weakness and histological abnormalities with abnormal muscle fibers and increased interstitial connective tissue. 31 There was a compensatory increase in MyHC IIa expression in the MyHC IId/x null mice.…”
Section: Discussionmentioning
confidence: 99%
“…There is accordingly reason to believe that this group of myopathies may have been misdiagnosed and lumped together with other neuromuscular disorders. Experimental animal studies have shown distinct patterns of muscle dysfunction in IIx and IIb MyHC null mice, while heterozygous mice are clinically normal (6). Missense mutation in the β/slow MyHC gene causes a familial hypertrophic cardiomyopathy-like disease in heterozygous mice, indicating that missense mutations are more deleterious than nulls (7).…”
Section: Introductionmentioning
confidence: 99%